Michelle Obama’s Impact on African American Women and Girls
XXXIII, 307 p. 5 illus.
Keywords: This edited collection explores how First Lady Michelle Obama gradually expanded and broadened her role by engaging in social, political and economic activities which directly and indirectly impacted the lives of the American people, especially young women and girls. The volume responds to the various representations of Michelle Obama and how the language and images used to depict her either affirmed, offended, represented or misrepresented her and its authors. It is an interdisciplinary evaluation by African American women and girls of the First Lady’s overall impact through several media, including original artwork and poetry. It also examines her political activities during and post-election 2016.